The Profile of Hospitalized Patients with Low Birth Weight Infants at RSUP Dr. M. Djamil Padang in 2018-2020 - Shabrina, Ranny; Lestari, Yuniar; Lisa, Ulfa Farrah (Journal of Ners and Midwifery, 2024)
Low Birth Weight (LBW) infants is the highest cause of neonatal death in Indonesia. LBW deaths are related to the baby's outcome which worsens his condition. LBW is grouped based on birth weight into LBW (1500-2499 grams), VLBW (1000-1499 grams), ELBW (<1000 grams), and each group shows a different neonatal outcome. This study aims to look at the profile of the group of low birth weight babies who are hospitalized at RSUP Dr.M.Djamil Padang. This research was a descriptive study by collecting medical record data from January 2018-December 2020. The data collection used total sampling 181 patients which were obtained and analyzed univariately. The results showed that out of 181 babies, 39.8% LBW, 37% VLBW, and 23.2% ELBW were found. Preterm gestational age is mostly in LBW (38.5%). Appropriate for Gestational Age (AGA) condition were mostly in VLBW (43.2%). APGAR scores at the 5th minute were normal mostly in LBW (48.3%). The most common comorbidity in LBW was hyperbilirubinemia (44.2%), in VLBW it was respiratory distress syndrome (45.1%), and in ELBW it was asphyxia (57.7%). Most NICU care was for VLBW (41.9%). Maternal breast milk combined with formula milk is the most common for LBW (49.3%). Most of the length of stay was 8-28 days for LBW (53.3%). Discharge from the hospital with a doctor's permission was mostly found in LBW (57.1%). Low birth weight babies were dominated by preterm gestational age, born at AGA, normal 5th minute APGAR score, had comorbid hyperbilirubinemia, received NICU care, received breastfeeding nutrition, had length of stay for 8-28 days, and discharged from the hospital with a doctor's permission.